Syntactic Tree Diagram: Students' Problems and the Causes - Sri Widyarti Ali (Universitas Veteran Bangun Nusantara, 2023)
Syntactic tree diagrams are used to help students recognize and analyze sentence structure. This study aims to discover students' difficulties in constructing syntactic tree diagrams of simple sentences. The descriptive qualitative approach was implemented with six English Department students participating as research participants. The data was gathered using interviews as the primary instrument and tests as a secondary instrument. The findings of this study show that students have six problems when constructing the syntactic tree diagram: determining phrase structure rules, placing words and phrases, determining word classes, drawing the diagram of long sentences, drawing arrows on the syntactic tree diagram, and identifying sentences with ambiguous meaning. Furthermore, some factors, such as insufficient knowledge of tree diagrams, the classroom environment, and a lack of confidence, contribute to students' difficulties in drawing the syntactic tree diagram of simple sentences. In light of the findings of this study, it is proposed that students practice constructing the syntactic tree diagram. Furthermore, lecturers are expected to give students more practice constructing syntactic tree diagrams in order to improve their ability to analyze sentence structure.